Validity of a speed detection system for measuring gait speed in community-dwelling older adults - Sirinun Boripuntakul (2020)
© 2019 Association for Computing Machinery. The objective of this study was to examine the concurrent validity of a speed detection system for measuring gait speed in healthy community-dwelling older adults. The participants comprised 15 healthy older adults with a mean age 67.00 ± 4.19 years. Participants walked over six-metre walkway at slow, usual, and fast paces. Two trials at each walking speed were performed. The gait speed for all walking conditions was measured concurrently with the motion analysis system. Pearson’s correlation coefficient was used to determine the correlation between the two systems with the significance level at p < 0.05. The results show that speed detection system measures have a good correlation with motion analysis system measures, with correlation coefficients between 0.975 and 0.980. Therefore, a speed detection system is proposed to be one of the useful methods to assess gait speed among older adults in both clinical and community settings.